(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study was to identify the intrinsic motivation level in experience levels, and individual and team sports athletes. The sample was composed by 448 athletes, in the age ranging from 16 to 18 years old, involved in: indoor football, team handball, volley-ball, karate, swimming, judo and track and field. The data were collected using the “Psychometrics Properties of Intrinsic Motivation Inventory for a Competitive Sports Settings” (McAULEY, DUNCAN and TAMMEN, 1989), using a stratified sample system, from 10% of the population. The data analysis was conducted using multifactor analysis of variance (ANOVA), in a predictive level of p<0,05. In order to identify the difference direction a multiple comparisons test (POST HOC SCHEFFE), was developed at 95% of probability. This results demonstrated that independent from sporting modality that the athlete involved in, the intrinsic motivation is psychological factor that no influence this variable. The results indicated a significantly differences in experience level variable. The conclusion of this study indicates that athletes for experience level, it was found greater intrinsic motivation level in medium experience level.